2008
DOI: 10.2478/s11535-008-0011-z
|View full text |Cite
|
Sign up to set email alerts
|

Antiapoptotic activity maintenance of Brain Derived Neurotrophic Factor and the C fragment of the tetanus toxin genetic fusion protein

Abstract: Neurotrophic factors have been widely suggested as a treatment for multiple diseases including motorneuron pathologies, like Amyotrophic Lateral Sclerosis. However, clinical trials in which growth factors have been systematically administered to Amyotrophic Lateral Sclerosis patients have not been effective, owing in part to the short half-life of these factors and their low concentrations at target sites. A possible strategy is the use of the atoxic C fragment of the tetanus toxin as a neurotrophic factor car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…These results are in accordance with the well-known potential of BDNF to enhance the survival of motoneurons in culture and in in vivo models of degeneration [39], presumably through the activation of anti-apoptotic signals, and with the neuroprotective effects of TTC demonstrated in vitro and in vivo , including the prevention of the stress-induced death of cultured neurons and the activation of survival signaling pathways [9,10,15,40]. Interestingly, BDNF-TTC-treated animals showed a similar protein expression pattern to TTC-treated animals, especially of active caspase-3 levels.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These results are in accordance with the well-known potential of BDNF to enhance the survival of motoneurons in culture and in in vivo models of degeneration [39], presumably through the activation of anti-apoptotic signals, and with the neuroprotective effects of TTC demonstrated in vitro and in vivo , including the prevention of the stress-induced death of cultured neurons and the activation of survival signaling pathways [9,10,15,40]. Interestingly, BDNF-TTC-treated animals showed a similar protein expression pattern to TTC-treated animals, especially of active caspase-3 levels.…”
Section: Discussionsupporting
confidence: 87%
“…We have also observed that TTC and the recombinant fusion protein BDNF-TTC inhibit apoptosis in cultured neurons, with the quimeric molecule being more effective than TTC alone [9]. BDNF may cause a relocalization of membrane domains containing TTC receptors by activating Trk receptors, thereby facilitating the neuronal internalization of TTC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study reported that some neurotrophic factors, in particular BDNF, facilitate the internalization of TTC recombinant molecules in motor nerve terminals [69]. In addition, TTC and the recombinant protein BDNF-TTC can inhibit apoptosis in cultured neurons, with the quimeric molecule being more effective than TTC alone [70]. Interestingly, BDNF may cause a relocalization of membrane domains containing TTC receptors by activating Trk receptors, thereby facilitating the neuronal internalization of TTC.…”
Section: Neuroprotective Properties Of Recombinant Molecules Of Ttc Imentioning
confidence: 99%